Access to antimalarial therapy: accurate diagnosis is essential to achieving long term goals. (7th July 2009) - Hopkins, Heidi; Asiimwe, Caroline; Bell, David
Abstract : Increased attention to and funding for malaria promises to improve access to effective treatment, but Heidi Hopkins, Caroline Asiimwe, and David Bell argue that without diagnostic testing much of this effort will be wasted